PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PERHUBUNGAN PROVINSI KALIMANTAN TIMUR - Mohammad Rayani; Safruddin Safruddin; Dodi Sukmayadi (Journal of Economic, Bussines and Accounting (COSTING), 2026)
The performance of civil servants (ASN) is an important indicator in realizing effective and high-quality governance, especially in public organizations that have a strategic role in public service. This study aims to analyze the influence of transformational leadership style and organizational climate on employee performance with job satisfaction as an intervening variable in the East Kalimantan Provincial Transportation Agency. This study uses a quantitative approach with a survey method, involving 131 respondents consisting of ASN and non-ASN employees. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling with a Partial Least Square approach (SEM-PLS) through the SmartPLS 4.0 application. The results of the study indicate that transformational leadership style and organizational climate have a positive and significant effect on employee job satisfaction. Job satisfaction is also proven to have a positive and significant effect on employee performance. In addition, transformational leadership style and organizational climate have a significant direct effect on employee performance. Indirect effect testing shows that job satisfaction acts as a significant mediating variable in the relationship between transformational leadership style and employee performance, as well as between organizational climate and employee performance. The coefficient of determination (R²) value shows that the model is able to explain 56.1% of the variation in employee performance and has good predictive ability. The findings of this study confirm that improving employee performance in public organizations depends not only on structural factors, but is also greatly influenced by leadership quality, a conducive organizational climate, and employee job satisfaction levels. This study is expected to contribute theoretically to the development of public sector human resource management studies and to serve as a basis for practical considerations and policies in efforts to continuously improve the performance of civil servants in local government.